Hubungan Algoritma Bezier dan B-Spline pada Fungsi Harmonisnya untuk Menciptakan Bentuk Kurva Sesuai Keinginan - Santoso, Djunaidy; Rasjid, Zulfany Erlisa; Irwansyah, Edy (Bina Nusantara University, 2011)
Computer graphics is a science widely used in any areas. Its up-to-date technique is applied to solve image problems related to needs of customer and decision-making. Images can be analyzed so as produce good form which its accuracy is still under researches using CAD and CAM. This study aims to associate algorithm Hermite, Bezier, B-Spline on its harmony function by creating a proper image to a form that can be used in drawing engineering for decision making. This study produces an adequate algorithm for image design.